Communication Ethics in the Telemarketer Team of PT Telmark Integrasi Indonesia - Ekowati Rahayuningsih; La Mani; Intan Pertiwi; Iwa Satya Soebrata; Dwi Kartika Nugraheni (Eduvest - Journal of Universal Studies, 2024)
Telemarketing is one method of marketing and socializing products using telephone media that is often used by companies. In this method, many results are not good in terms of sales due to the lack of understanding of good communication ethics from marketers. Communication ethics have an important role in maintaining professionalism and achieving goals in the telemarketing team. PT Telmark Integration Indonesia is a company engaged in BPO (Business Process Outsourcing), with one of the services provided is sales through telemarketing. This study aims to analyze the practice of communication ethics applied in the telemarketing team at PT Telmark Integration Indonesia. The research methods used are interviews with telemarketing team members and document analysis of policies and guidelines related to communication ethics. The results showed that with improved, more intensive training factors on communication ethics, effective conflict management, as well as awareness of the importance of privacy and security of customer data that the telemarketing team at PT Telmark Integrasi Indonesi can improve the results of telemarketing.